THE FIRST REPORT ON THE FRESHWATER MALACOFAUNA OF NEWASA TAHSIL FROM UPPER GODAVARI BASIN, MAHARASHTRA - G.S.PANDE; S.R. PATIL (The Bioscan, 2020)
The Newasa tahsil is an important administrative block within Ahmednagar district, Maharashtra. Although small in area, the Newasa tahsil is drained by the Godavari, the longest river of South India. The tahsil is known for its vast sugarcane fields and sugar factories. This area also has a rich network of canals, seasonal ponds, and backwaters of the famous Nathsagar dam. The area has great potential for harboring aquatic mollusks. With no record of any previous study on malacofauna, the present study was undertaken to investigate the diversity, distribution and importance of the freshwater malacofauna of Newasa tahsil. The study included a malacofaunal survey of 9 different water bodies which included rivers, canals, ponds, and lakes. A total of 17 different species of freshwater mollusks were recorded. The mollusks species recorded include 12 gastropods representing 5 families and 9 genera. The bivalves recorded include 5 species representing 2 families and 2 genera. The study is highlighted by the new locality record for Amerianna carinata as it is recorded for the first time from the Godavari river. Many of the gastropod species recorded in the present study have been reported earlier to be of medical, veterinary, and economic importance.